Evaluation of Valuable Metal Recycling Behavior using Nickel Sulfate Waste Solution and Pre-Treatment by-Products Recovered from Waste Lithium-Ion Batteries - Joo, Soyeong; Im, Byoungyong; Kim, Dae-Guen (Archives of Metallurgy and Materials, 2026)
In this study, high-crystallinity nickel metal powder was synthesized from a nickel sulfate solution recovered from Lithium-Ion Batteries (LIBs) waste via a continuous precipitation-liquid phase reduction process. The effects of hydroxide precipitation conditions and reducing agent concentration on phase formation, crystallinity, and particle morphology were systematically investigated. Nickel hydroxide was first prepared as an intermediate product by controlling the [OH]/[Ni] molar ratio using sodium hydroxide as a precipitant, followed by liquid-phase reduction with hydrazine to produce metallic nickel powder. Single-phase nickel metal powder was obtained under [OH]/[Ni] = 7–14 conditions, with average particles sizes ranging from 4.05 to 4.35 μm.